Feminisme Dalam Wacana Studi Islam - M. Karman (ISLAMICA, 2015)
Gender discourse is interesting in the melee of Islamic thought. Islamic literatures have different views about gender. Classical Islamic literature generally arranged in the perspective of culture androcentric --- man became the measure of all things (man is the measure of all things) --- if measured in modern, many of which can be assessed gender-biased due to the strengthening system of patriarchal culture that developed in the community. The culture of patriarchy (male dominated) has put women in a subordinate position of men. Male superiority that is contained in almost all the patriarchal system often curb the norms of justice and egalitarianism offered by women for the sake of male power. The patriarchal culture system has been presenting the practices of anti-emancipation of women in society. Indeed, women are ideologically still assumed to serve as a "friend behind". Women seemed only to know the problems of the kitchen so many of them, to say nothing of the whole, less direct role in the public sectors. In contrast to the classical Islamic literature which is dominated by patriarchal culture system, in Islamic literature modern / contemporary women are no longer in subordinated position to men. Women have equal status and equal (the same) with men. From this came the bearers of feminism whose occurrence is not solely concerned about issues of ladies, but also began to fly the flag of the women's movement, although only the early signals. Feminists struggling to find the root cause of a strong patriarchal system embedded in society and making women alienated and oppressed.